2015
DOI: 10.1007/s10967-015-4493-7
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of plutonium on a novel thin film for use in spectrometry

Abstract: Trace elemental and isotopic analysis of actinides via Thermal Ionization Mass Spectrometry (TIMS) is often difficult and time consuming due to intensive sample preparation. Polymer thin films show strong potential for rapid concentration of radionuclides from solution that may prove as suitable substrates for TIMS analyses. In this work, a polymer thin film (~180 nm) was coated onto a silicon substrate and utilized for rapid radioanalytical analysis. The polymer is composed of poly(vinyl benzyl chloride) func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…To reduce the time to prepare an alpha spectrometry source, we and others have turned to developing Pu extractive membranes that can concentrate Pu to detectable limits and serve directly as the sample source. Membranes are functionalized for Pu capture either by casting a polymer-ligand film onto the membrane surface, or by utilizing a reactive surface from which a ligand layer can be grafted [5][6][7][8][9][10]. By keeping the functional layer relatively thin, high spectral resolutions can be achieved that rival electrodeposited sources.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the time to prepare an alpha spectrometry source, we and others have turned to developing Pu extractive membranes that can concentrate Pu to detectable limits and serve directly as the sample source. Membranes are functionalized for Pu capture either by casting a polymer-ligand film onto the membrane surface, or by utilizing a reactive surface from which a ligand layer can be grafted [5][6][7][8][9][10]. By keeping the functional layer relatively thin, high spectral resolutions can be achieved that rival electrodeposited sources.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques involve sample dissolution, concentration, and extraction using high-affinity thin films and sample analysis by alpha spectrometry. Extraction of plutonium and other actinides is achieved using functionalized thin films that have a very high affinity for actinide adsorption [14][15][16][17]. The thin films are functionalized by covalent incorporation of specific functional groups onto the polymer structure or the immobilization of ligands with high binding affinity for actinides in the rigid structures of inert polymers.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, functionalized polymer films and thin-film composite membranes have been demonstrated for the extraction and screening of various radioisotopes in water. Combined with alpha spectrometry, these substrates greatly reduce the time involved for isotopic screening by combining purification, concentration, and sample mounting steps. Approaches to developing the functionalized polymer thin films fall into two general categories, the first being physical immobilization or encapsulation of extractive ligands into a polymer matrix, akin to how an extractive chromatography resin is formed.…”
mentioning
confidence: 99%